Eksplorasi Bakteri Pendegradasi Timbal Pada Tanah Tercemar Air Lindi dari Tempat Pemrosesan Akhir (TPA) Sampah Perkotaan - F Fatmawati; Muhammad Ammar; S Suherman (Fapetrik-UMPAR, 2021)
Waste containing heavy metals is an environmental issue and is a concern of many parties. Heavy metal ions/compounds come from various activities such as the metal production industry, metal plating, mining operations, and leather tanning. Metal waste is one type of inorganic waste that we often encounter in Final Processing Sites due to the continuous accumulation of waste and produce pollutants in the form of leachate. Leachate has the potential to contaminate groundwater. This study aims to explore and identify morphologically bacteria obtained from soil contaminated with leachate and can degrade hazardous and toxic materials on waste containing heavy metals. Soil samples were taken from the landfill soil at TPA Tamangapa, Makassar, taken as a composite sample, while the bacterial isolation used the steak plate method. The research stages included bacterial cultivation, morphological tests, and calculating the number of colonies using the Total Plate Count (TPC) method. The results showed that 10 pure bacterial isolates could grow on NA media enriched with 5ppm lead metal.